Upaya Peningkatan Pengetahuan dan Keterampilan Kelompok Wanita Tani Kenanga Lestari Desa Pucang Banjarnegara tentang Teknik Budidaya Sayuran Hidroponik - Sarno Sarno; Fanny Tri Raditya (Universitas Mathla'ul Anwar Banten, 2020)
EFFORTS TO INCREASE KNOWLEDGE AND SKILLS KENANGA LESTARI WOMEN’S FARMER’S GROUP OF PUCANG VILLAGE BANJARNEGARA ABOUT HYDROPONIC VEGETABLES TECHNIQUE. Kenanga Lestari Women's Farmers Group is the only group consisting of 20 farmer women in Pucang Village, Banjarnegara. The farmer women's group continues to exist to develop verticulture of organic vegetable cultivation by utilizing home yards since 2017. Since the beginning the caretaker and members of the farmer women's group still have limited knowledge and skills, especially about hydroponic vegetable cultivation techniques. The aim of the activity is to transfer science and technology about the cultivation of hydroponic vegetables in an effort to increase the knowledge and skills of farm women groups. It is also intended to encourage increased income and welfare of farmer women groups. The method used includes 3 methods, namely; (a) public education methods through extension activities on hydroponic systems and hydroponic vegetable cultivation techniques; (b) science and technology diffusion methods through training activities on hydroponic vegetable cultivation techniques; (c) advocacy method that is to provide assistance at the end of the activity. The results of the activity showed that the knowledge and skills of the administrators and members of the Kenanga Lestari farmer group increased from previous conditions regarding organic vegetable cultivation techniques.